Persepsi Peserta Didik pada Keefektifan Penggunaan Media Pembelajaran Online di Masa Pandemi Covid-19 dalam Perspektif Interaksional - Wulan, Puja Damar; Lindawati, Yustika Irfani (Lembaga Yasin AlSys, 2022)
The Covid-19 pandemic has brought changes, especially in the field of education., one of which is the implementation of online learning using certain learning media. Learning media is a tool used for the learning process. This study aims to determine students’s perceptions of the effectiveness of using online learning media at SMA Negeri 2 Pandeglang. This type of research is descriptive qualitative with research subjects 6 students of SMA Negeri 2 Pandeglang, using data collection techniques of observation, interviews, and analysis of primary data and secondary data. Data analysis techniques used are dara reduction, data presentation, and drawing conclusions. The results of this study indicate that each student’s perception has its own perception of the effectiveness of online learning media on sociological subjects that are carried out boldly, including (1) bold learning conditions in the use of learning media which sometimes cause various obstacles or difficulties faced by students, (2) the effectiveness of bold learning in the use of online learning media, namely the use of Google Classroom and WhatsApp applications as learning media for the chosen sociology subject is effective for creating an interesting and easy-to-follow learning atmosphere, so that learning objectives can be achieved according to the criteria for complete learning has been determined, (3) the theory of symbolic interactionism regarding bold learning in the use of learning media, namely the use of symbols in applications that are used as interactions between educators and students through media a online based learning.